THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY (K3), WORKLOAD AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT PERKEBUNAN NUSANTARA IV PABATU - Mutiara Shauma; Novi Punggahani; Rumiris Siahaan; Cia Cai Cen (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Occupational Health and Safety (OHS), Workload, and Physical Work Environment on Employee Performance at PT Perkebunan Nusantara IV Pabatu. The research employed a quantitative approach with a population of 282 employees in the harvesting division and a sample of 74 respondents, determined using the Taro Yamane formula. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 25. The results indicate that, partially, OHS and Workload do not have a significant effect on Employee Performance, with significance values ​​of 0.356 and 0.389, respectively. However, the Physical Work Environment variable has a significant effect on Employee Performance, with a significance value of 0.012. Simultaneously, the three variables (OHS, Workload, and Physical Work Environment) have a significant influence on Employee Performance, with an F-value of 3.403 and a significance level of 0.022. The adjusted R² value of 0.090 indicates that 9% of the variation in Employee Performance can be explained by these three variables. These findings highlight the importance of managing the physical work environment effectively to improve performance, although attention to OHS and workload remains essential as part of a comprehensive human resource management strategy.